MENGUNGKAP MEKANISME SOSIAL DI BALIK STUNTING: STUDI KUALITATIF TENTANG KEMISKINAN STRUKTURAL, BUDAYA KONSUMSI, DAN PENGASUHAN LINTAS GENERASI DI DESA CIAMBAR, SUKABUMI - Nurhayati Nurhayati; Muhammad Fathurrahman; Koramen Haulian Sirait; Ni Putu Ayu Laksmi Subadra (Journal Economics Technology And Entrepreneur, 2025)
This study aims to understand how socio-economic conditions, food consumption patterns, intergenerational childcare practices, environmental sanitation, and access to integrated health posts (Posyandu) interact to shape stunting risk among children under five. An intrinsic case study design with a qualitative approach was employed. Thirteen informants—comprising parents, two Posyandu cadres, and the village head were purposively selected. Data were collected through in-depth interviews, participant observation, and document review, then analyzed thematically using NVivo 12. Findings reveal that unstable income, a "just full enough" consumption orientation, caregiving by grandmothers with limited nutrition literacy, inadequate sanitation,& irr egular Posyandu utilization collectively form social mechanisms that incr ease stunting risk. Word frequency analysis identified "Alhamdulillah" as a cultural coping mechanism that normalizes food insecurity. The study concludes that addressing stunting requires multi-level, family- and community-based interventions integrating food security, nutrition educa tion, sanitation improvement, and strengthened Posyandu functions.